2020
DOI: 10.1016/j.bbi.2020.04.081
|View full text |Cite
|
Sign up to set email alerts
|

The distress of Iranian adults during the Covid-19 pandemic – More distressed than the Chinese and with different predictors

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
183
9
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(224 citation statements)
references
References 5 publications
23
183
9
9
Order By: Relevance
“…Taken together, the results suggest distinct predictor patterns for healthcare staff's mental health in Iran versus China, resonating with an earlier study of an Iranian public sample (Jahanshahi et al, 2020). Jahanshahi et al (2020) reasoned that "different countries vary in their medical systems, the availability of personal protective equipment (PPE), cultures, labor and employment conditions, the policies of lockdown, the ease of working from home and maintaining a living in a pandemic, and the information in both mainstream and social media". Our results corroborate their suggestions and call for future research to identify mental health predictors for the public and healthcare staff in different countries during the COVID-19 pandemic.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Taken together, the results suggest distinct predictor patterns for healthcare staff's mental health in Iran versus China, resonating with an earlier study of an Iranian public sample (Jahanshahi et al, 2020). Jahanshahi et al (2020) reasoned that "different countries vary in their medical systems, the availability of personal protective equipment (PPE), cultures, labor and employment conditions, the policies of lockdown, the ease of working from home and maintaining a living in a pandemic, and the information in both mainstream and social media". Our results corroborate their suggestions and call for future research to identify mental health predictors for the public and healthcare staff in different countries during the COVID-19 pandemic.…”
supporting
confidence: 85%
“…COVID-19 hit Iran early and hard (Jahanshahi et al, 2020). The first confirmed case in Iran appeared on 19 February 2020, and active cases rise quickly since then, overwhelming healthcare workers.…”
mentioning
confidence: 99%
“…The results of this study showed 35.50% of the cases with mild COVID-19 related stress and 9.30% with severe COVID-19 related stress. Similar results were found in Chinese and Iranian population (18,19), but the frequencies were smaller when compared to those obtained in Brazilian population (20). Regarding the obtained values for PHQ-9 and GAD-7, the results of this study showed similar and comparable results with those obtained in Chinese population.…”
Section: Discussionsupporting
confidence: 87%
“…The COVID-19 peritraumatic distress index (CPDI) was rst applied in China (18) and lately validated in other countries (i.e. Brazil, Iran and Peru) (19,20). This instrument was designed for a population to evaluate changes related to mood, behavior, cognitive skills, circadian rhythm and other somatic symptoms due to the COVID-19 pandemic.…”
Section: Covid-19 Peritraumatic Distress Index (Cpdi)mentioning
confidence: 99%
“…Women, compared to men, were more likely to report worsened components of anxiety and depression on the HADS. These findings have been replicated, in varying age-groups and from different countries including the UK ( 18 ), Demark ( 14 ), Spain ( 19 , 23 , 43 ), Italy ( 21 ), Turkey ( 44 ) and Iran ( 20 , 22 ). Furthermore, studies conducted on the effects of stress, have consistently reported women to be at increased risk of developing anxiety and depression ( 45 ).…”
Section: Discussionmentioning
confidence: 78%